Novel approaches to representing the speed–time characteristics of a direct start-up induction machine driving gravitational-type loads - Ilija Knežević; Tatijana Dlabač; Martin Ćalasan; Maja Krčum (Brodogradnja)
On ships, practically all types of induction machine loads are present, among which those with fan and gravitational characteristics are the most common. This paper addresses the speed–time curve dependency on the direct start of an induction machine under gravitational load. The characteristic of speed–time, ω = f (t), is described through two analytical expressions. The first expression is derived using the formula for torque based on Thévenin’s equivalent circuit, while the second expression is derived from Kloss’s formula for torque. The mathematical model has been tested through simulation and experimental validation on an induction machine in laboratory conditions. Also, the paper includes a realised MATLAB program for determining the mentioned characteristics. The results show the high precision and practical applicability of the proposed analytical expressions in different working conditions.